Impact of a hospital improvement initiative in Bangladesh on patient experiences and satisfaction with services: two cross-sectional studies - Omer Khalid; Cockcroft Anne; Andersson Neil (BMC, 2011)
Abstract Background The Bangladesh government implemented a pilot Hospital Improvement Initiative (HII) in five hospitals in Sylhet division between 1998 and 2003. This included management and behaviour change training for staff, waste disposal and procurement, and referral arrangements. Two linked cross-sectional surveys in 2000 and 2003 assessed the impact of the HII, assessing both patients' experience and satisfaction and public views and use of the hospitals. Methods In each survey we asked 300 consecutive outpatients and a stratified random sample of 300 inpatients in the five hospitals about waiting and consultation time, use of an agent for admission, and satisfaction with privacy, cleanliness, and staff behaviour. The field teams observed cleanliness and privacy arrangements, and visited a sample of households in communities near the hospitals to ask about their opinions and use of the hospital services. Analysis examined changes over time in patients' experience and views. Multivariate analysis took account of other variables potentially associated with the outcomes. Survey managers discussed the survey findings with gender stratified focus groups in each sample community. Results Compared with 2000, an outpatient in three of the hospitals in 2003 was more likely to be seen within 10 minutes and for at least five minutes by the doctor, but outpatients were less likely to report receiving all the prescribed medicines from the hospital. In 2003, inpatients were more likely to have secured admission without using an agent. Although patients' satisfaction with several aspects of care improved, most changes were not statistically significant. Households in 2003 were significantly more likely to rate the hospitals as good than in 2000. Use of the hospitals did not change, except that more households used the medical college hospital for inpatient care in 2003. Focus groups confirmed criticisms of services and suggested improvements. Conclusion Improvements in some aspects of patients' experience may have been due to the programme, but the decreased availability of medicines in government facilities across the country over the period also occurred in these hospitals. Monitoring patients' experience and satisfaction as well as public views and use of hospital services is feasible and useful for assessing service interventions.